Methods of converting digital signals to analog (continuous) signals and their essence" to link teaching to pedagogical technologies. (Global Scientific Review, 2023)
A scientific article on the topic “Circuit design and microprocessor systems” is devoted to the issues of “Methods for converting digital signals into analog (continuous) signals and their essence”, advanced interactive methods and the use of innovative educational technologies in teaching